If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -30x + -1(-3) * 6 = -3(3x + 1) Multiply -1 * -3 -30x + 3 * 6 = -3(3x + 1) Multiply 3 * 6 -30x + 18 = -3(3x + 1) Reorder the terms: 18 + -30x = -3(3x + 1) Reorder the terms: 18 + -30x = -3(1 + 3x) 18 + -30x = (1 * -3 + 3x * -3) 18 + -30x = (-3 + -9x) Solving 18 + -30x = -3 + -9x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '9x' to each side of the equation. 18 + -30x + 9x = -3 + -9x + 9x Combine like terms: -30x + 9x = -21x 18 + -21x = -3 + -9x + 9x Combine like terms: -9x + 9x = 0 18 + -21x = -3 + 0 18 + -21x = -3 Add '-18' to each side of the equation. 18 + -18 + -21x = -3 + -18 Combine like terms: 18 + -18 = 0 0 + -21x = -3 + -18 -21x = -3 + -18 Combine like terms: -3 + -18 = -21 -21x = -21 Divide each side by '-21'. x = 1 Simplifying x = 1
| 1+1-2p+4p=-48 | | 2x^2+4x=12+x^2 | | 5y+3x=-15 | | (28000+3000)x=(36000+2000)x | | 11m-6=20+m | | 27=15+N+3(N) | | S=-16t^2+64+80 | | 25+100(12-x)=5(2x-7) | | -5/6x-7= | | 5x+(-y)+8+(-6x)+9y= | | 8y=8y+24 | | 600m=1500 | | 6y-2=30 | | 0.625(y-14)=.25(y+12) | | 6(k-5)+7(7k-3)=4 | | 5x-8x-14=35 | | x^2-17xy-18y^2=0 | | 56=7(-3x+2) | | 11x-9=6x+6 | | 3s^2-5s^2+s-6s= | | -6=-4(5+7n)-7(n+3) | | -qr+7qr= | | (y^2-6)(8y^2-9y+8)= | | 12x+15=12x-9 | | x+3y=-36 | | 19=-3(8-7v)-(4v+8) | | 5x-2(4x-7)=35 | | 3(5x+2)-3=15x+3 | | -12=6-6x+8x-8 | | 7.69-(-2.5)(-4)=-2.31 | | 12a^2+5a= | | 7f+10f=-90 |